Relationship between the central alpha-adrenoceptors and central effects of morphine - Fu Shao-xuan; Zhang Shi-shan; Jin Yuan; Li Yun-shan (Acta Pharmacologica Sinica, 2016)
In conscious rats, noradrenaline given intracerebroventricularly(icv) exhibited marked antidiuretic effect and antagonized the antidiuretic effect of morphine administered subcutaneously(sc). Although icv clonidine had no apparent-effect on the urine volume, it antagonized the antidiuretic effect of morphine. Both phentolamine and phenoxybenzamine given icv showed antidiuretic effect and enhanced the morphine-induced antidiuretic action.Phenoxybenzamine,yohimbine or phentolamine given by icv route showed antinociceptive effect in mice using the hot-plate method. The sc ED50 for morphine analgesia was significantly reduced when icv ED20 analgesic doses of phenoxybenzamine. These results suggested that the functional state of central alpha-adrenoceptors could modify the central effects of morphine, and that the morphine analgesia was more closely related with the attenuation of central adrenoceptor activity in the post-synaptic alpha-adrenoceptive sites.